Effects of Eichhornia Crassipes Infested Pond on Growth of Clarias Gariepinus (Burchell 1822) in Concrete Ponds - Ngodigha, Sabina Alatari (International Journal of Contemporary Sciences (IJCS), 2024)
Concrete tanks measuring 3.0 m x 2.0 m x 1.2 m were stocked with African catfish and infested with water hyacinth at 0%, 10%, 20%, and 30% plant cover to evaluate the effect of water hyacinth on fish growth. The stocking density was 5 fish/m², with an average weight of 10.3 g and an average total length of 10.4 cm. The study lasted 60 days, during which the fish were fed twice daily for six days a week. Weekly, random samples were taken from each tank to measure body weight and length, and water quality parameters were also analyzed. The results indicated that all water quality parameters remained within acceptable limits. However, the final average weight of fish was lower in the control and at 30% plant cover. The study concludes that African catfish grow better in ponds moderately infested with water hyacinth.